2015
DOI: 10.1371/journal.pone.0117548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Radiotherapy Treatment Planning in the Presence of a Magnetic Valve Tissue Expander

Abstract: The combination of radiotherapy treatments and breast reconstruction, using temporary tissue expanders, generates several concerns due to the presence of a magnetic valve inside the radiation field. The objective of this work is to evaluate a radiotherapy treatment planning for a patient using a tissue expander. Isodose curve maps, obtained using radiochromic films, were compared to the ones calculated with two different dose calculation algorithms of the Eclipse radiotherapy Treatment Planning System (TPS), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…After all, immediate reconstruction of any type- autologous or implant-based-- may prolong oncologic treatment time or complicate radiation treatment planning. 21, 25, 26 Moreover, further research is needed to determine if radiation accessibility of lymph nodes, particularly the internal mammary chain, is affected by having a deflatable expander versus permanent implant in place, which is an area of active controversy. Thus, managing these patients in collaboration with surgical, medical, and radiation oncologists is essential to providing the best reconstructive and oncologic management.…”
Section: Discussionmentioning
confidence: 99%
“…After all, immediate reconstruction of any type- autologous or implant-based-- may prolong oncologic treatment time or complicate radiation treatment planning. 21, 25, 26 Moreover, further research is needed to determine if radiation accessibility of lymph nodes, particularly the internal mammary chain, is affected by having a deflatable expander versus permanent implant in place, which is an area of active controversy. Thus, managing these patients in collaboration with surgical, medical, and radiation oncologists is essential to providing the best reconstructive and oncologic management.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo film measurement one side at a time for one PMRT patient treated with 15 MV beams concurred with ex vivo results, while TLD measurements for six patients treated with 15 MV beams showed smaller dose variation (86%~101% of prescription dose). They recommended using 15 MV photons with compensating bolus to treat patients; Chatzigiannis et al17 used Monte Carlo (MC) simulation and found 7% to 13% dose reduction with the expander in place for two 6 MV tangential photon beams, and around 6% dose reduction for 18 MV beams; Chen et al18 reported that tissue expanders with metal ports will increase dose heterogeneity and reduce dose coverage significantly for patients treated with 6 MV or 18 MV opposed tangent photon fields; Sharabi et al reported in an abstract19 5%~20% dose attenuation due to the metallic port and claimed a nondeformable implant model of the port was created based on manufacture specifications, but they did not show the details of the model or validate the dosimetric accuracy of the model; Trombetta et al20 initially reported that no significant change in dose distributions was found for an opposed pair of 6 MV photon beams delivered to a breast phantom containing a metallic port, but later drew a conflicting conclusion in a separate paper21 that the metallic port must be taken into account in the dose calculations; Strang et al22 used TLD measurements and concluded that radiation doses around the tissue expander were unaltered; Srivastava et al23 conducted measurements in a water phantom using a small ion chamber (IC) and concluded that dose perturbation caused by metallic port in photon beams was 5%~20% and this perturbation could not be predicted by TPS; Zabihzadeh et al24 used MC simulation and found a dose enhancement about 15% in front of the port and a dose reduction of about 10% at 5 cm under the port; Gee et al25 used radiochromic films as in vivo dosimeter and found an average 7% dose reduction to skin surface in a sample of PMRT patients with the tissue expander present during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…There are also various new devices being used such as internal magnetic metallic ports which may be placed within temporary tissue expanders [4, 5]. The risks of undergoing implant based reconstruction include scarring at the interface between the implant and the tissue, capsular contracture, infection, pain, skin necrosis, fibrosis, and impaired wound healing, and the chance of these complications developing seems to be higher in patients who also receive radiotherapy [2, 10].…”
Section: Discussionmentioning
confidence: 99%
“…These patients are classified as high risk if they have T3/T4 tumours and/or ≥4 positive lymph nodes [1, 3]. Radiotherapy usually commences approximately four to eight weeks after the mastectomy [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation